Volumetric imaging of the developing prepubertal mouse uterine epithelium using light sheet microscopy. Issue 5 (3rd May 2018) - Vue, Zer; Gonzalez, Gabriel; Stewart, C. Allison; Mehra, Shyamin; Behringer, Richard R.
Abstract : Endometrial or uterine glands secrete substances essential for uterine receptivity to the embryo, implantation, conceptus survival, and growth. Adenogenesis is the process of gland formation within the stroma of the uterus. In the mouse, uterine gland formation initiates at postnatal day (P) 5. Uterine gland morphology is poorly understood because it is primarily based on two‐dimensional (2D) histology. To more fully describe uterine gland morphogenesis, we generated three‐dimensional (3D) models of postnatal uterine glands from P0 to P21, based on volumetric imaging using light sheet microscopy. At birth (P0), there were no glands. At P8, we found bud‐ and teardrop‐shaped epithelial invaginations. By P11, the forming glands were elongated epithelial tubes. By P21, the elongated tubes had a sinuous morphology. These morphologies are homogeneously distributed along the anterior–posterior axis of the uterus. To facilitate uterine gland analyses, we propose a novel 3D staging system of uterine gland morphology during development in the prepubertal mouse. We define five uterine gland stages: Stage 1: bud; Stage 2: teardrop; Stage 3: elongated; Stage 4: sinuous; and Stage 5: primary branches. This staging system provides a standardized key to assess and quantify prepubertal uterine gland morphology that can be used for studies of uterine gland development and pathology. In addition, our studies suggest that gland formation initiation occurs during P8 and P11. However, between P11 and P21 gland formation initiation stops and all glands elongate and become sinuous. We also found that the mesometrial epithelium develops a unique morphology we term the uterine rail.